Study of using Moringa Oleifera seeds as natural coagulant for turbidity removal in kitchen wastewater - WEI FAN, LING (Progress in Engineering Application and Technology, 2022)
Nowadays, kitchen wastewater becomes an environmental issue that can cause negative impacts on human health and the environment since it becomes deteriorates each year without proper treatment. In order to reduce this issue, M.Oleifera seeds which act as natural coagulants were used to take place in the coagulation process so that the turbidity can be reduced effectively. The water parameters such as coagulant dosage, stirring speed, and settling time were manipulated in the Jar test experiment to analyze the efficiency of the M.Oleifera at the end of the study. Results obtained depicted that the optimum coagulant dosage was 2.5 g/L with turbidity removal 83.55%, stirring speed was 120 rpm with turbidity removal 53.23% and settling time was 30 minutes with turbidity removal 43.79%. As a result, it can be inferred that M.Oleifera seeds powder can be utilized as a natural coagulant alternative to synthetic coagulants.